Implementation of Integrated Marketing Communication Based on Purchase Intention in The Artisan Tea Marketing Program - Syahban, Khofifah Rahmat; Marsasi, Endy Gunanto (Jurnal Manajemen Bisnis, 2024)
This study delves into a plantation industry company operating with B2B and B2C marketing but needs more digital marketing expertise. Their production base is situated in Wonosobo Regency, known for supplying raw materials to market leaders, positioning them as market followers. PT. Perkebunan Teh Tambi introduced the "Volka" brand's Tea Artisan program. The primary aim of this research is to formulate the company's digital marketing strategy. Qualitative research methods such as in-depth interviews, direct observations, document collection, and secondary data analysis within the company's marketing division are utilized. The ultimate goal is to aid the company's market expansion through digital marketing, improving Purchase Intention via Integrated Marketing Communication theory, with an anticipated optimization of digital marketing's utility.